Pengaruh Pemberian Arang Sekam Padi dan Pupuk NPK Terhadap Ketersediaan Unsur Hara N, P, K dan Hasil Tanaman Bawang Merah di Tanah Gambut - Utama, Redian Risky Septi; Sulakhudin, Sulakhudin; Nusantara, Rossie Wiedya (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2025)
Peat soil is acidic with an average pH below neutral. This is a challenge for farmers to utilize the vast amount of peat soil in West Kalimantan. Ameliorants used from materials that are easily available and can reduce dependence on the use of factory fertilizers. Husk charcoal is one of the organic materials that can increase nutrients and the combination of NPK fertilizer can increase shallot production. This study aims to see the effect of rice husk charcoal and NPK on planting shallot plants on peatlands. The research was conducted by planting 9 treatment samples on peat soil using a predetermined dose of rice husk charcoal and NPK fertilizer with 3 repetitions of each treatment. The research design used a complete factorial randomized design with the first factor being the dose of rice husk charcoal and the second factor being the dose of NPK fertilizer. From the results of this study, the largest dose of rice husk charcoal and NPK fertilizer is 700g/polybag of rice husk charcoal and 10g/polybag of NPK fertilizer is the most optimal dose for shallot plants grown in peat soil by increasing soil N-total, bulb weight, bulb diameter and bulb length of shallot plants.